MULTIPHASE FLOW IN A POROUS MEDIUM USING LATTICE BOLTZMANN METHOD AND GRID VERIFICATION - Ashirbekov, Assetbek (Nazarbayev University School of Engineering and Digital Sciences, 2022)
Lattice Boltzmann Method (LBM) of computational fluid dynamics is well suited for small-scale modeling, operating at mesoscale. LBM with a pseudopotential model and pressure equation of state is used to develop a model of the flow of CO2 immiscibly displacing water in a porous medium simulating the fundamental problem of CO2 sequestration. Validation of the model numerical stability is performed with droplet tests. The possibility of a nonunity viscosity ratio is explored, which was found possible, but to an extend limited by increased miscibility. Grid size verification procedure is developed for the model, for the first time in literature.
Keywords: Lattice Boltzmann Method; LBM; type of access: open access; grid verification; multiphase flow; porous medium